Sca-1+ Cardiosphere-Derived Cells Are Enriched for Isl1-Expressing Cardiac Precursors and Improve Cardiac Function after Myocardial Injury - Ye, Jianqin; Boyle, Andrew; Shih, Henry; Sievers, Richard E.; Zhang, Yan; Prasad, Megha; Su, Hua; Zhou, Yan; Grossman, William; Bernstein, Harold S.; Yeghiazarians, Yerem (PLOS ONE, 2012)
Background Endogenous cardiac progenitor cells are a promising option for cell-therapy for myocardial infarction (MI). However, obtaining adequate numbers of cardiac progenitors after MI remains a challenge. Cardiospheres (CSs) have been proposed to have cardiac regenerative properties; however, their cellular composition and how they may be influenced by the tissue milieu remains unclear. Methodology/Principal Finding Using “middle aged” mice as CSs donors, we found that acute MI induced a dramatic increase in the number of CSs in a mouse model of MI, and this increase was attenuated back to baseline over time. We also observed that CSs from post-MI hearts engrafted in ischemic myocardium induced angiogenesis and restored cardiac function. To determine the role of Sca-1+CD45- cells within CSs, we cloned these from single cell isolates. Expression of Islet-1 (Isl1) in Sca-1+CD45- cells from CSs was 3-fold higher than in whole CSs. Cloned Sca-1+CD45- cells had the ability to differentiate into cardiomyocytes, endothelial cells and smooth muscle cells in vitro. We also observed that cloned cells engrafted in ischemic myocardium induced angiogenesis, differentiated into endothelial and smooth muscle cells and improved cardiac function in post-MI hearts. Conclusions/Significance These studies demonstrate that cloned Sca-1+CD45- cells derived from CSs from infarcted “middle aged” hearts are enriched for second heart field (i.e., Isl-1+) precursors that give rise to both myocardial and vascular tissues, and may be an appropriate source of progenitor cells for autologous cell-therapy post-MI.